Saxifraga luoxiaoensis (Saxifragaceae), a new species from Hunan and Jiangxi, China - Zhang, Xin-Jian; Liu, Zhong-Cheng; Meng, Kai-Kai; Ding, Qiao-Ling; Wang, Lei; Liao, Wen-Bo (Phytotaxa, 2018)
Saxifraga luoxiaoensis, a new species of the genus Saxifraga sect. Irregulares (Saxifragaceae) from Hunan and Jiangxi, China, is described and illustrated. This new species is most similar to S. daqiaoensis, which can be easily distinguished from the later by its leaf margin 7- or 9-lobed and winged capsule. The systematic position of this species within Saxifraga sect. Irregulares is assessed based on molecular phylogenetic analysis of the chloroplast regions sequences together with morphological comparisons.